PENINGKATAN LITERASI BACA DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING PADA SISWA KELAS IV SD - Helga Nahakleky; Zainudin Notanubun; Stelie Dorce Ratumanan (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The results of the 2022 Programme for International Student Assessment (PISA) show that Indonesia's reading literacy score is only 359 points, far below the OECD average of 476 points. Similar problems were also found at Kaiwatu Christian Elementary School, particularly among fourth-grade students who had difficulty understanding the content of the reading material, determining the main ideas, and retelling the content of the text they had read. This study aims to improve the reading literacy of fourth-grade students at Kaiwatu Christian Elementary School through the application of the Cooperative Learning model. This study uses the Classroom Action Research (CAR) method, which is carried out in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects were 17 fourth-grade students at Kaiwatu Christian Elementary School in Southwest Maluku Regency. The research instruments used included tests and observation sheets with data collection techniques through observation, tests, and documentation. The success indicator was set at a minimum of 75% of students achieving a score of 65 according to the KKTP standard. The results of the study indicate that the application of the Cooperative Learning model can significantly improve students' reading literacy. At the beginning of the pre-cycle, the average score of students was only 60 with a mastery rate of 18% or 3 students. In Cycle I, the average score remained at 60, but the number of students in the “Poor” category decreased from 35% to 12%. A significant improvement occurred in Cycle II, with the average score increasing to 80 and the mastery rate reaching 100% or 17 students. The improvement was comprehensive, covering cognitive, psychomotor, and affective aspects. It can be concluded that the application of the Cooperative Learning model is proven to be effective in improving the reading literacy of fourth-grade students at Kaiwatu Christian Elementary School ABSTRAK Hasil Programme for International Student Assessment (PISA) tahun 2022 menunjukkan bahwa skor literasi membaca Indonesia hanya mencapai 359 poin, jauh di bawah rata-rata negara OECD sebesar 476 poin. Permasalahan serupa juga ditemukan di SD Kristen Kaiwatu, khususnya pada siswa kelas IV yang mengalami kesulitan dalam memahami isi bacaan, menentukan gagasan pokok, dan menceritakan kembali isi teks yang telah dibaca. Penelitian ini bertujuan untuk meningkatkan literasi baca siswa kelas IV SD Kristen Kaiwatu melalui penerapan model Cooperative Learning. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah 17 siswa kelas IV SD Kristen Kaiwatu Kabupaten Maluku Barat Daya. Instrumen penelitian yang digunakan meliputi tes dan lembar observasi dengan teknik pengumpulan data melalui observasi, tes, dan dokumentasi. Indikator keberhasilan ditetapkan apabila minimal 75% siswa mencapai nilai 65 sesuai standar KKTP. Hasil penelitian menunjukkan bahwa penerapan model Cooperative Learning dapat meningkatkan literasi baca siswa secara signifikan. Pada kondisi awal pra-siklus, rata-rata nilai siswa hanya mencapai 60 dengan persentase ketuntasan 18% atau 3 siswa. Pada Siklus I, rata-rata nilai tetap 60 namun jumlah siswa kategori Kurang menurun dari 35% menjadi 12%. Peningkatan signifikan terjadi pada Siklus II dengan rata-rata nilai meningkat menjadi 80 dan ketuntasan mencapai 100% atau 17 siswa. Peningkatan terjadi secara komprehensif meliputi aspek kognitif, psikomotor, dan afektif. Dapat disimpulkan bahwa penerapan model Cooperative Learning terbukti efektif dalam meningkatkan literasi baca siswa kelas IV SD Kristen Kaiwatu..